Montenegrina' tangerine responses to liming and to organic and mineral fertilizers - Panzenhagen, Nestor Valtir; Koller, Otto Carlos; Sartori, Ivair Antonio; Portelinha, Nelso Volcan (Pesquisa Agropecuaria Brasileira, 1999)
The objectives of the present study were to investigate the influence of liming and mineral and organic fertilization on yields of cv. 'Montenegrina' tangerines (Citrus deliciosa Tenore) grafted onto Poncirus trifoliata Raf. The grove was planted in July of 1988 on a Dark-Red Podzolic (Rhodic Paleudult) soil. The experiment was set up in randomized blocks design composed of nine treatments and four replicates, with three plants per plot. The treatments were: control (without liming and fertilizers); soil acidity neutralization to pH 6,5 before planting; annually poultry manure and liming; annually cattle manure and liming; annually N and K fertilizers and liming; annually N and K fertilizers, liming and P fertilizer before planting; annually N, P and K fertilizers and liming; annually N, K and double the rate of P, and liming; annually N, P and K fertilizers without liming. The results showed that P application before planting were sufficient to maintain adequate fruit yield up to eight years after planting. The increases of leaf N contents was positively related to increases in production and to decreases of the average fruit weight. The ammonium sulphate application acidifies the soil, and requires a greater quantity of liming support.
Keywords: Citrus deliciosa; plant nutrition